Advancing primary care to promote equitable health: implications for China - Hung, Li-Mei (BioMed Central, 2012)
China is a country with vast regional differences and uneven economic development, which have led to widening gaps between the rich and poor in terms of access to healthcare, quality of care, and health outcomes. China's healthcare reform efforts must be tailored to the needs and resources of each region and community. Building and strengthening primary care within the Chinese health care system is one way to effectively address health challenges. This paper begins by outlining the concept of primary care, including key definitions and measurements. Next, results from a number of studies will demonstrate that primary care characteristics are associated with savings in medical costs, improvements in health outcomes and reductions in health disparities. This paper concludes with recommendations for China on successfully incorporating a primary care model into its national health policy, including bolstering the primary care workforce, addressing medical financing structures, recognizing the importance of evidence-based medicine, and looking to case studies from countries that have successfully implemented health reform.